2021
DOI: 10.1021/acs.analchem.1c03985
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Contact pH Sensor with Covalent Attachment of Ionophores and Ionic Sites to a Poly(decyl methacrylate) Matrix

Abstract: With a view to improving the sensor lifetime, solid-contact ion-selective electrodes (ISEs) were prepared with a plasticizer-free and cross-linked poly(decyl methacrylate) matrix, to which only the ionic sites, only the ionophore, or both the ionic sites and ionophore were covalently attached. In earlier work with covalently attached ionophores or ionic sites, it was difficult to discount the presence of ionophores or ionic site impurities that were not covalently attached to the polymer backbone because the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…No attempt was made to covalently attach the ionic sites to the PDMA backbone, as it has been shown that ISEs with both the ionophore and the ionic sites covalently attached exhibit larger electrical resistances and excessive response times and are not suitable for potentiometric analysis. [19] We note that leaching of the ionic sites Angewandte Chemie Forschungsartikel from these sensing membranes is only possible by transfer of these very hydrophobic anions along with protons into the sample, a process that is also hindered by the strong affinity of the protons to the ionophore. [3] Indeed, this is the reason why in this work we chose to covalently attach the ionophore and not the ionic sites.…”
Section: Performance Of Potentiometric Devicesmentioning
confidence: 97%
See 4 more Smart Citations
“…No attempt was made to covalently attach the ionic sites to the PDMA backbone, as it has been shown that ISEs with both the ionophore and the ionic sites covalently attached exhibit larger electrical resistances and excessive response times and are not suitable for potentiometric analysis. [19] We note that leaching of the ionic sites Angewandte Chemie Forschungsartikel from these sensing membranes is only possible by transfer of these very hydrophobic anions along with protons into the sample, a process that is also hindered by the strong affinity of the protons to the ionophore. [3] Indeed, this is the reason why in this work we chose to covalently attach the ionophore and not the ionic sites.…”
Section: Performance Of Potentiometric Devicesmentioning
confidence: 97%
“…Because of its methacrylate group, this ionophore is incorporated into the PDMA polymer backbone in the course of the photoinitiated polymerization. [19] The ionic site tetrakis(pentafluorophenyl)borate, which is required to provide membrane permselectivity for cations, [3] was included into the photografting solution in a 1 to 3 molecular ratio to the ionophore. No attempt was made to covalently attach the ionic sites to the PDMA backbone, as it has been shown that ISEs with both the ionophore and the ionic sites covalently attached exhibit larger electrical resistances and excessive response times and are not suitable for potentiometric analysis.…”
Section: Performance Of Potentiometric Devicesmentioning
confidence: 99%
See 3 more Smart Citations